2009
DOI: 10.1002/ppap.200800108
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Polymer Surfaces Compatible with a CMOS Process for Direct Covalent Enzyme Immobilization

Abstract: Plasma polymerized surfaces, prepared using a CMOS compatible plasma enhanced chemical vapor polymerization technique, are found to covalently immobilize enzymes without the need for intermediate chemical linker groups. The polymerized surfaces are smooth, strongly adherent to substrates, and have a long shelf life for storage. After incubation with enzymes, a densely packed monolayer is attached. We report the effects of both oxygen etching and annealing post‐processing showing that they can be implemented so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…The plasma polymers and plasma-modified surfaces created using energetic ion bombardment reported more recently are even more hydrophilic (Yin et al 2009e;Kondyurin et al 2009b) than the most hydrophilic surface studied in the earlier works, but nevertheless show much higher levels of SDS-resistant protein attachment (see, for example, MacDonald et al 2008;Yin et al 2009d;Nosworthy et al 2007;Kondyurin et al 2008b, c;Bax et al 2009), rivalling those observed on the most hydrophobic of surfaces examined in the earlier studies. Figure 4 shows where the data obtained on the energetic ion-treated surfaces lie in relation to the adsorption curve of Kiaei et al (1992).…”
Section: Retention Of Activity After Freeze Dryingmentioning
confidence: 66%
See 3 more Smart Citations
“…The plasma polymers and plasma-modified surfaces created using energetic ion bombardment reported more recently are even more hydrophilic (Yin et al 2009e;Kondyurin et al 2009b) than the most hydrophilic surface studied in the earlier works, but nevertheless show much higher levels of SDS-resistant protein attachment (see, for example, MacDonald et al 2008;Yin et al 2009d;Nosworthy et al 2007;Kondyurin et al 2008b, c;Bax et al 2009), rivalling those observed on the most hydrophobic of surfaces examined in the earlier studies. Figure 4 shows where the data obtained on the energetic ion-treated surfaces lie in relation to the adsorption curve of Kiaei et al (1992).…”
Section: Retention Of Activity After Freeze Dryingmentioning
confidence: 66%
“…These properties are retained when nitrogen is added while the covalent binding capacity is reduced with oxygen or hydrogen additions, even though the ESR signal is strong in both cases (Yin et al 2009e). This loss of binding capacity could be explained by a reduction in the mobility of unpaired electrons when hydrogen or oxygen are present in the structure.…”
Section: Surface Structure Of Plasma Prepared Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma-based approaches have gained considerable interest for immobilization of biomolecules, since they do not require complicated wet chemical steps to achieve binding allowing linker-free immobilization [13]. Moreover, in some conditions lowered stability of bioactive molecules due to usage of spacers can be prevented [14]. A key challenge for the plasma treatment process is aging as a result of post-plasma oxidation initiated by the reaction between remaining radicals and in-diffusing atmospheric oxygen as well as the movement of some of the polymer chains from the surface into the bulk [15].…”
Section: Introductionmentioning
confidence: 99%